2010
DOI: 10.1007/s00198-010-1239-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns of antioxidant vitamin and carotenoid intake associated with bone mineral density: findings from post-menopausal Japanese female subjects

Abstract: The combination of vitamin C and β-cryptoxanthin may be associated with radial BMD in post-menopausal Japanese female subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 43 publications
5
93
3
2
Order By: Relevance
“…Results showed that the retinol pattern, determined by a high intake of preformed retinol, zeaxanthin, vitamin E, lutein, vitamin C, and b-carotene antioxidants, was negatively associated with BMD (18). In contrast, the b-cryptoxanthin pattern, rich in b-cryptoxanthin and vitamin C (18), and the dietary pattern high in folate; total fiber; vitamin B-6; potassium; vitamins A, C, and K; b-carotene; magnesium; copper; and manganese (21) were positively associated with BMD. The nutrient-dense dietary pattern high in all macro-and micronutrients, especially manganese, potassium, phosphorous, calcium, iron, vitamin B-12, folate, vitamin C, vitamin E, and alcohol, and the southwestern French dietary pattern, reflecting high consumption of proteins, fats, alcohol, phosphorous, calcium, vitamin D, vitamin B-12, and retinol, were associated with a lower risk of fractures (33).…”
Section: Data-driven Dietary Patternsmentioning
confidence: 81%
See 4 more Smart Citations
“…Results showed that the retinol pattern, determined by a high intake of preformed retinol, zeaxanthin, vitamin E, lutein, vitamin C, and b-carotene antioxidants, was negatively associated with BMD (18). In contrast, the b-cryptoxanthin pattern, rich in b-cryptoxanthin and vitamin C (18), and the dietary pattern high in folate; total fiber; vitamin B-6; potassium; vitamins A, C, and K; b-carotene; magnesium; copper; and manganese (21) were positively associated with BMD. The nutrient-dense dietary pattern high in all macro-and micronutrients, especially manganese, potassium, phosphorous, calcium, iron, vitamin B-12, folate, vitamin C, vitamin E, and alcohol, and the southwestern French dietary pattern, reflecting high consumption of proteins, fats, alcohol, phosphorous, calcium, vitamin D, vitamin B-12, and retinol, were associated with a lower risk of fractures (33).…”
Section: Data-driven Dietary Patternsmentioning
confidence: 81%
“…Studies were conducted in >20 countries: Australia (16,44), Brazil (24), Canada (25,26,32), China (22,28,30,34,49,55), France (33,56), Greece (14), Iran (20,21,48), Ireland (19), Italy (38), Japan (13,18,31), Korea (23,27,29,40,43,53,54), Netherlands (51), Norway (45), Portugal (41,60), Scotland (17), Spain (47), Sweden (59), United Kingdom (15,39), United States (35-37, 42, 46, 52, 58), and 10 European countries (57).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations